Draft Annual plan 1994-95 Statements Union Territory of Lakshadweep - Planning Commission (Planning Commission, 1994)
Progress of Expenditure during the Annual Plan 1993- 1994 ( Proposed outlay for the Annual Plan 1994-95 -do- (M.N.P) Physical targets and achievement during the Annual Plan 1993-94 & Proposals for the Annual Plan 1994-95 -do- (M.N.P)Proposals for spill over and on-going programmes/Projects Proposals for Maximising Benefits of Completed project/programme Proposals for Programmes/Projects-New Schemes of Eighth Plan.
Union Territory of Lakshadweep, Planning Department